Per una storia del rapporto tra alimentazione e diversità culturali - Di Giacinto, Maura (Studi sulla Formazione/Open Journal of Education, 2013)
In the human experience the main values in the supply system are results of strong cultural, economic, social and environmental conditioning and of cultural processes; the act of feeding represents clearly a behavior – language and the single food are the words. What does it means then, in the third millennium, to support the belief that food is synonym of culture? Does is it still make sense to talk about a one supply culture in a always more complex and differentiated background for style of consume and multiethnic composition?